DIABETIC KETOACIDOSIS AS THE INITIAL PRESENTATION OF TYPE 1 DIABETES IN CHILDREN AND ADOLESCENTS: EPIDEMIOLOGICAL STUDY IN SOUTHERN BRAZIL - Souza,Leonardo Calil Vicente Franco de (2020)
ABSTRACT Objective: To analyze the variables associated with the presence of diabetic ketoacidosis in type 1 diabetes mellitus (T1DM) diagnosis and its impact on the progression of the disease. Methods: We reviewed the records of 274 children and adolescents under 15 years, followed in a Pediatric Endocrinology clinic of a university hospital in Curitiba-PR. They had their first appointment between January 2005 and April 2015. Results: Most patients received their T1DM diagnosis during a diabetic ketoacidosis episode. The associated factors were: lower age and greater number of visits to a physician’s office prior to diagnosis; diabetic ketoacidosis was less frequent in patients who had siblings with T1DM and those diagnosed at the first appointment. Nausea and vomiting, abdominal pain, tachydyspnea, and altered level of consciousness were more common in the diabetic ketoacidosis group. There was no association with socioeconomic status, duration of symptoms before diagnosis, and length of the honeymoon period. Conclusions: Prospective studies are necessary to better define the impact of these factors on diagnosis and disease control. Campaigns to raise awareness among health professionals and the general population are essential to promote early diagnosis and proper treatment of diabetes mellitus in children and adolescents.